Sistem Pengamanan Ponsel melalui Penyaringan Kata dengan Metode Levenshtein Distance - Adnan Zulkarnain; Poerbaningtyas E; Dwify O Risqoni (Prosiding SISFOTEK, 2021)
In this digital era, there are a lot of smartphone users, especially children and teenagers. With this smartphone, there are various kinds of information media that can be obtained easily through various online media such as online games, online information media, social media, pornography very easily. The ease of accessing various kinds of online media often occurs in technology such as for violence and for pornography. It is this background that requires a security system on cellphones/smartphones through words that apply the Levenshtein Distance method. The purpose of this study is to provide security for children to avoid accessing links that are not liked by children. The results of the research on testing the word assessment feature for each word typed into the keyboard by applying the Levenshtein Distance method. The filtered words are as expected, which is reaching 100%, which is very effective to use. So that the use of smartphones, especially among children and adolescents, can be more controlled in accessing information.